A Surgeon’s Insight on Kala Pareeksha with the Aid of Gurvadi Gunas - S Balasubramaniam; Rengapadmini B; Anita Patel (International Journal of Ayurveda and Pharma Research, 2022)
The physicians around the world would have come across the patients complaining of a particular symptom arising in a particular time of the day or night, or similar complaints recurring around the same months for the past few years, in their clinical practice. The classical texts of Ayurveda have described Kala as a factor influencing pathogenesis, diagnosis and treatment of a disease. The term “Kala” indicates Rogi avastha as well as the time. Though the texts have given the details of various seasons along with the changes that the Doshas undergo in each of them and the regimens to follow respectively, the description of Dosha avasthas with respect to day and night is very limited. Acharya Sushruta, the father of surgery has given a key insight on this principle. Ayurvedic diagnosis and treatments cannot be standardized in a very broad scale but rather its approach should be target- specific, for which we need deeper analysis for the principles. For achieving this, a Guna based analysis of every aspect of the protocol is to be followed while diagnosing and treating the patient (Guna Pratyaneeka pareeksha and Chikitsa), a process which unearths the hidden secrets of Ayurveda. This article deals the concept of Kala pareeksha in terms of day, night and a season from the basis of Gunas rather than the basis of Doshas with respect to the references from mainly Sushruta Samhita and Ashtanga Hrudaya in a way showing the actual beauty of the ever-puzzling science we are striving to practice.